OC-046 Outcome of acute severe ulcerative colitis: data from the UK National IBD Audit. (23rd September 2015) - Arnott, I D R; Leiper, K; Down, C; Lowe, D; Potter, J; Rhodes, J M
Abstract : Introduction: Acute severe ulcerative colitis (UC) is a medical emergency requiring hospitalisation. Approximately one third of patients will not respond to therapy and will need colectomy during the hospital admission. Data examining mortality, efficacy of therapy, treatment selection and outcomes often come from specialised units with relatively few data examining outcomes in larger less selected populations. The UK National IBD Audit collected data on over 6000 adult patients admitted to UK hospitals with IBD. Aim: To assess outcomes for patients with acute severe ulcerative colitis in the 2008 National IBD Audit. Methods: All hospitals that admitted IBD patients in the UK were invited to take part. Sites completed a questionnaire detailing service at 1 September 2009. Sites were asked to audit 40 set of case notes of patients that were admitted with IBD between 1/09/07 and 31/08/08. Acute severe UC was defined by the Truelove and Witts criteria. Results: 209 sites submitted data, with a 93% participation at Trust/Health board level. Data were collected on 6135 patients (3154 CD and 2981 UC). Of the 2981 patients with UC, there were 863 with acute severe disease (465 males, median age 41 years (IQR 28–58 years). Inpatient mortality was 1.2% with death being strongly associated with increased age (p<0.001), male sex (p=0.02), C. Diff infection (p<0.04) and if first line medical treatment fails the risk of death increases to 2.8%. 61.1% responded to first line treatment with steroids. Of the 317 who failed treatment with steroids 108 underwent surgery without further medical treatment, 98 were treated with cyclosporine and 52 with infliximab. The response rate to infliximab was higher than that to cyclosporine (75% vs 46%, p=0.0009). Overall 163 underwent surgery with a median time to surgery of 10 days (IQR 7–14 days). The post operative mortality did not differ between those coming to surgery before and after 7 days following admission. Conclusion: The inpatient mortality of acute severe UC in the UK remains appreciable and strongly associated with age and the presence of C. Diff infection. The risk of death doubles if first line medical therapy fails. In this data set, response rates to infliximab are greater than cyclosporin although the results of ongoing clinical trials will give further data. Effective communication between medical and surgical teams, clear decision making and timely surgery will help keep mortality to a minimum.